Donation of oocytes as treatment for infertility in patients with premature ovarian failure. Awarded the "Nicolau de Moraes Barros" prize for gynecology - Franco Júnior, José Gonçalves (1994)
A total of 7 cycles of embryo transfer by oocyte donation were performed on 5 patients with premature ovary failure (POF). All donors were under 35 of age and the recipients average age was 38.6 years. For synchronization between donor and recipient a semi programmed menstrual cycle was used by means of oral contraceptive followed by ovarian stimulation of donor with clomiphene citrate and human menopausal gonadotrophin. The recipients were easily adjusted to the donors by a flexible model of gradually increasing doses of estradiol valerianate. The average number of oocytes donated was 3.14 and average embryo cleavage rate was 80.2%. The average number of embryos transferred was 2.57. Embryo implantation rate was 22.2%. Clinical gestations occurred in 57.1% of the cycles. This series is probably the first one in Brazilian literature on oocyte donation as treatment for infertility in patients with premature ovarian failure.